Trends of land system in Ukraine - Tretiak, A.; Tretiak, V. (Land Management, Cadastre and Land Monitoring, 2017)
The organization of land use in different countries is characterized by a variety of land system types, those proved their effectiveness in certain countries, but not are necessarily as effective in others. The objective factors that led to the emergence of various models of the land system, include socio-economic, historical, ethnic, cultural, natural and other features of different countries and peoples that inhabit them. During 1991-2016 years,Ukraineestablished basics of a new land order and the respective land relations and the system of market-oriented land use, especially in agriculture. It is characterized by: a new legal and regulatory framework, different types of ownership of land and other natural resources, a multi-structure and paid land use, providing public with land parcels, initiated the establishment of a market-oriented system of state land cadastre, including registration of land parcels and rights to them. So, modern land transformations in Ukraine, which laid the basics of a new land order, requires the development of new approaches to land use management at different hierarchical levels of general land planning throughout the country. It caused by many reasons. Primarily: setting the state boundaries and bounds of administrative units; development of different types of land ownership; increased numbers of new landowning and land tenure of citizens, enterprises, institutions and associations up to more than 23 million; need for separation of state and municipal property for land; establishment of payment for land use; specification of legal and functional status of land and of various restrictions, encumbrances and easements to each individual land parcel. It is hard to overemphasize the importance of work on land-use planning at different hierarchical levels and general land management in modern conditions. Particularly acute need of land planning in urban and agricultural land use sectors of the country. Thus, the strategic development of land reforms and bringing them to a new level - the volume and long-term task that requires scientific substantiation of a rational state land policy. The study justified that the land order - a land system, i.e. a set of measures for the territorial organization of land and other natural resources of the country, land relations, that is determined by system of ownership and use of land, as well as by the principles of organization of territory. In the process of land reform the land system have been changed several times: from the system of administrative-territorial division and respective to it forms of land use and methods of land use (collective and state farms) as of year 1990, to the system of the administrative-territorial division with the respective forms of land ownership (state, collective, private) and the forms and methods of land use (collective and state farms, collective farms, peasant (farmer) farms, subsidiary farms, collective gardens, agricultural research institutions, subsidiary agriculture enterprices, etc.) as of 1991 - 2001. As of the 2002 - 2016 , the land order in Ukraine was defined: by the natural-resource-based division and natural-economic-based division (zoning); by the administrative-territorial division; by the forms of land ownership (state, municipal, property of foreign countries, co-ownership, private ownership of individuals and of legal entities); by the forms and methods of land use (for example, in agriculture there were the non-state agricultural enterprises such as collective, cooperative, corporate (agricultural holdings), companies, private-rental farms, subsidiary farms, private (family and individual), state and municipal scientific research and others). Today, due to the decentralization of power, the new model for land order is developed, which will be presented in subsequent studies. Keywords. Land system, administrative-territorial structure, forms of land ownership, land use